Association between smoking status and health-related quality of life: a study on differences among age groups - Zhong, Guanping; Shu, Yang; Li, Hongwei; Zhou, Yuelin; Wei, Qiaoying; Yang, Biao; Yang, Lian (Frontiers in Public Health, 2025)
PurposeThis study explored the effect of four different smoking statuses (non-smokers, moderate smokers, heavy smokers, and former smokers) on health-related quality of life (HRQOL) among residents aged 15 years and older in Sichuan Province, China with consideration of potential differences among age groups (young, middle-aged, and older adults).MethodsThe EQ-5D-5L utility index and EQ-VAS score were used to measure HRQOL. Self-reporting and salivary cotinine test were used to determine the smoking status of respondents, and the Tobit regression model was used to explore the relationship between smoking status and HRQOL.ResultsThe Tobit regression model found a significant correlation between smoking status and HRQOL. Heavy smokers reported a lower EQ-VAS score compared to non-smokers (p < 0.01); the EQ-5D-5L utility index and EQ-VAS score reported by former smokers were lower compared to non-smokers (p < 0.05 and p < 0.01, respectively). In the young population, the EQ-VAS score of heavy smokers was lower than that of non-smokers (p < 0.05); In the middle-aged population, the EQ-VAS score of heavy smokers was lower than that of non-smokers (p < 0.05). The EQ-5D-5L utility index and EQ-VAS score of former smokers were lower than that of non-smokers (p < 0.05 and p < 0.001, respectively). However, in the older adult population, the EQ-5D-5L utility index and EQ-VAS score of moderate smokers were higher compared to non-smokers (p < 0.05 and p < 0.05, respectively).ConclusionThis study found a significant correlation between HRQOL and smoking status, with notable differences in the relationship between smoking, EQ-5D-5L utility index, and EQ-VAS scores across age groups. We recommend targeted measures to control tobacco use based on age, considering specific smoking risks for each group. In particular, attention should be paid to the harm of smoking among young and middle-aged groups, reduce the occurrence of smoking behavior through publicity and early intervention, and provide appropriate health interventions for the older adult group. In addition, effective smoking cessation support policies should be developed to encourage residents to quit or reduce smoking frequency, avoid the progression of moderate smoking to heavy smoking and thus lead to serious health threats.